The physico-chemical properties of fullerenes and porphyrin derivatives deposited on conducting surfaces - Murphy, Barry E. (Trinity College (Dublin, Ireland). School of Physics, 2014)
In this thesis, three organic molecules are examined on three distinct surfaces by a variety of surface science techniques, foremost among them being scanning tunneling microscopy (STM). When deposited on the W02/W(110) surface, C60 fullerenes self-assemble into islands which grow from the substrate’s inner step edges, forming a close- packed monolayer. At some bias voltages, chains of molecules sit topologically lower in height than others, because they lie in the grooves between the WO2 nanorows. When the sample is imaged at room temperature, all C60 are spinning too fast for the STM to resolve, and so appear as featureless spheres. However, when cooled to 78K, the molecules’ motion is frozen and their inner orbital structure can be seen.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin